Degradation of a poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) compound in different environments - Pavlo Lyshtva and Viktoria Voronova and Jelena Barbir and Walter Leal Filho and Silja Denise Kröger and Gesine Witt and Lukas Miksch and Reinhard Sabowski and Lars Gutow and Carina Frank and Anita Emmerstorfer-Augustin and Sarai Agustin-Salazar and Pierfrancesco Cerruti and Gabriella Santagata and Paola Stagnaro and Cristina D'Arrigo and Maurizio Vignolo and Anna-Sara Krång and Emma Strömberg and Liisa Lehtinen and Ville Annunen (Heliyon, 2024)
Poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) is a promising biodegradable bio-based material, which is designed for a vast range of applications, depending on its composite. This study aims to assess the degradability of a PHBV-based compound under different conditions. The research group followed different methodological approaches and assessed visual and mass changes, mechanical and morphological properties, spectroscopic and structural characterisation, along with thermal behaviour. The Ph-Stat (enzymatic degradation) test and total dry solids (TDS)/total volatile solids (TVS) measurements were carried out. Finally, the team experimentally evaluated the amount of methane and carbon dioxide produced, i.e., the degree of biodegradation under aerobic conditions. According to the results, different types of tests have shown differing effects of environmental conditions on material degradation. In conclusion, this paper provides a summary of the investigations regarding the degradation behaviour of the PHBV-based compound under varying environmental factors. The main strengths of the study lie in its multi-faceted approach, combining assessments of PHBV-based compound degradability under different conditions using various analytical tools, such as visual and mass changes, mechanical and morphological properties, spectroscopic and structural characterization, and thermal behavior. These methods collectively contribute to the robustness and reliability of the undertaken work.
Keywords: PHBV; Polymer blends; Degradation; Natural environment; Laboratory scale testing; Morphological properties